Elite incomes around the world: Command over tradables, non-tradables, and people - Paul Segal; Michail Moatsos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper analyses elite incomes around the world, and how international comparisons of elite incomes vary depending on the exchange rate and income concept used. It is well known that between-country income inequality is higher using market exchange rates than purchasing power parity (PPP) exchange rates, due to a combination of traded sector bias and the BalassaSamuelson effect, and we confirm that this is the case for comparing elite incomes across countries. In contrast, we argue that using entitlements over labour (ELs) as a measure of real incomes of elites leads to the opposite effect; since the non-traded sector is relatively labour-intensive, incomes in the sense of ELs demonstrate non-traded sector bias relative to PPP incomes. They therefore provide a complement, or opposite bound, to the traded-sector bias of market exchange rates. Consistent with this argument, we find that between-country inequality among global elites is indeed lower using ELs than either PPP or market exchange rates. But elite incomes in ELs do not merely converge-elites in poorer countries leapfrog or overshoot their rich country counterparts, enjoying higher real incomes in terms of their command over domestic labour. The explanation for this is the higher levels of inequality in poorer countries.
Keywords: D31; D63; 330; elites; income inequality; Balassa-Samuelson effect; PPP exchange rates; entitlements over labour